(untitled) (Journal of Hama University, 2022)
This study was aimed to detect the lumpy skin disease in cows in Syria, after several foci appeared in Lattakia and Hama governorates, which led to heavy economic losses in cow herds. These flocks suffered from the appearance of diffuse nodules on the skin with fever, lacrimal secretions, and enlarged lymph nodes. Nodules and whole blood samples were taken from these animals, and after DNA extraction, they were subjected to polymerase chain reaction (PCR) using primers specific to the (RPO30) gene. The result of the (PCR) revealed the detection of the lumpy skin disease virus in all skin samples and in all the animals on which nodules appeared, and the virus was not detected in the blood of these animals. Whereas, the virus was detected in the blood of the animals in contact with them, which only showed a slight fever and tear secretions, but without the appearance of skin nodules. These results clearly show the possibility of detecting the (LSDv) using (PCR) and based on the (RPO30) gene early and befor the appearance of specific symptoms that characterize the disease, and this may allow to reduce economic losses.